At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I was given y2/y1 = y3/y2 then it is a exponential function and if its y2 - y1 = y3-y2 it is a linear function
have u tried that?
I'm just confused by these problems it also brings up delta x = x2 - x1 and x2 - x1 = x3 - x2 Do these equations have to do wit the continuity of the function I'm trying to determine?
I'm not trying to get the answer for this problem I simply just want a better understanding of the problem itself
probably, i'm not an expert at this but i'll try to get u someone who can help :)
Working on this....
It's not that difficult. I just haven't done this in a while so I'm going to contact a resource and get back to you.
Okay, I'm back. It really is easy and I should have remembered how to do it, but I got stuck on one thing.
Basically, when dealing with exponential functions, they have the general form: y = ab^x, where a = initial value and b = base or growth factor. If b > 1, then the function is exponential growth. If 0 < b < 1, meaning if b is between 0 and 1, then the function is exponential decay. Also, b = 1 + r, where r = the percent rate of change. In this particular case, we have the set of table values for 3a). To find out if the function is exponential, simply take the f(x) values and divide the values like so: 43.5/87 = 0.5 87/174 = 0.5 The fact that both divisions equal 0.5 indicates an exponential function. Using the formula for exponential functions, y = ab^x, we first find a. Since x = 0 and 6 y = f(x) = 43.5, 43.5 = a, the initial value. Now, we must find b. To find b, plug in a given point along with a into the formula, then solve for b as follows: y = ab^x 87 = 43.5b^1 87/43.5 = b 2 = b So, now that we've found a and b, we can now write our exponential formula: y = 43.5(2)^x 3b) is just a linear equation. I'm sure you can figure that one out yourself.
If you have any questions, let me know.
thanks hero, I'm not too good at this but that made a lot of sense :) thanks :)